Oxford handbook of cardiac nursing - Olsen, Kate, 1967- (Oxford : Oxford University Press, 2020)
This handbook provides a systematic account of the main areas of cardiac nursing including assessment, investigation, treatment, rehabilitation, and pharmacological interventions. Cardiac nurses in all settings will find this a practical and evidence-based summary of the relevant issues related to the appropriate care of their patients.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 25, 2020).
Keywords: Heart -- Diseases -- Nursing